Kajian Perbaikan Pengelolaan Sampah Kota Palangka Raya dalam Perspekti Praktis dan Pendidikan - Muhamad Yusuf (Pencerah Publik, 2015)
This research aims to study the waste management system in Palangka Raya City and map the system of Division of Service territory and its collection system and socialization of the garbage management and Focus Group Discussion (FGD) model in the environment School in the community of Palangka Raya. In this study use qualitative Descriptive. The Data collected, arranged in a manner tailored to the needs of analysis. The data collected consists of secondary data and primary data. Secondary data collected from related installations, while the primary data collection is implemented by survey method. For the purposes of data and information that is macro-special is used Rapid Rural Appraisal (RRA) approach, while micro-data is used in-depth interviews (Deep Interview) using questionnaires. The results of the research conducted, there is an improvement in the management of the city scale Palangka Raya. In relation to the need to improve the organizational structure of management that is integrated and cross-sectoral to increase community participation and improvement of service